Nanoparticles and the new era in diabetes management - Woldu, Minyahil A.; Lenjisa, Jimma L. (International Journal of Basic & Clinical Pharmacology, 2017)
Diabetes mellitus (DM) has been known to mankind for more than 2000 years. DM is a group of metabolic disorder characterized by a complete lack of insulin, a relative lack of insulin, or insulin resistance. The increase in prevalence of DM is due to three influences: lifestyle, ethnicity, and age. Current challenges in diabetes management include: optimizing the use of the already available therapies to ensure adequate glycemic, blood pressure, and lipid control and to reduce complications. At present several researches have been focusing on new management options for diabetes. Among these options the use of nanomedicine is becoming an eye catching and most promising. The aim of the present review is to provide brief overview of the applications of nanoparticles (NPs) in diabetes management. The development of improved oral insulin administration is very essential for the treatment of DM to overcome the problem of daily subcutaneous injections. In diabetic patients oral administration of insulin can be beneficial not only to alleviate the pain and trauma caused by injections, but it can also mimic the physiological fate of insulin as well. It has been found that NPs of chitosan, calcium pectinate zinc oxide, alginate, casein and different polymers have been used as a carrier for oral insulin delivery. Buccal administration of insulin with absorption enhancers showed a maximum 12% pharmacological activity. Biodegradable Polymeric NPs for parenteral insulin delivery have also been used, where the insulin matrix surrounded by the nanoporous membrane containing grafted glucose oxidase. A rise in blood glucose level triggers a change in the surrounding nanoporous membrane, resulting in biodegradation and subsequent insulin delivery. Inhalable, polymeric NP-based drug delivery systems have also been tried earlier for the treatment of tuberculosis and cardiovascular disease treatment. Such approaches can be directed toward insulin delivery through inhalable NPs. All previous studies resulted in post treatment accumulation of the NPs in skin and eyes. These drug delivery technologies are in various stages of research and development. The medical applications for nanotechnology are enormous and could give medicine, including the treatment of diabetes, an entirely new outlook.